2000
DOI: 10.1177/1532673x00028003002
|View full text |Cite
|
Sign up to set email alerts
|

Policy Conflict and the Structure of Interest Communities

Abstract: Drawing on data from a survey of 595 state interest representatives this article asks: Is policy conflict widespread in state interest communities or is it rare due to the isolation of interest organizations in relatively placid niches? Two contending perspectives frame the current debate on this issue. Whereas Browne maintains that balkanization characterizes interest communities, Salisbury and his colleagues suggest that many policy domains feature substantial intergroup interaction, conflict, and cooperatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 9 publications
(13 reference statements)
2
19
0
Order By: Relevance
“…4 Other scholars have concentrated more on the domain-level implications of the issue niches argument. In particular, Nownes (2000) cast doubt on the proposition that balkanization is a property of all policy domains. Relying on a survey of 595 lobbyists in three states, he demonstrated that focusing narrowly on specific issues does not allow groups to avoid conflict.…”
Section: Identity and The Issue Nichementioning
confidence: 99%
See 1 more Smart Citation
“…4 Other scholars have concentrated more on the domain-level implications of the issue niches argument. In particular, Nownes (2000) cast doubt on the proposition that balkanization is a property of all policy domains. Relying on a survey of 595 lobbyists in three states, he demonstrated that focusing narrowly on specific issues does not allow groups to avoid conflict.…”
Section: Identity and The Issue Nichementioning
confidence: 99%
“…Scholars have focused on the questions of whether the macro-structures of policy domains are balkanized (e.g., Baumgartner & Leech, 2001;Haider-Markel, 1997;Nownes, 2000) and whether the desire to form issue niches is a strategic motivator at the group level (e.g., Heaney, 2004;Hojnacki, 1997). However, the question of how interest groups build their identities on Capitol Hill has been subject to relatively little scrutiny.…”
mentioning
confidence: 99%
“…This finding was not expected, considering the findings of previous studies of state and national policy domains (see Heinz et al 1993;Nownes 2000). Big city citizen groups, many of which presumably go "head to head" with business groups, report relatively low levels of conflict.…”
Section: Big City Citizen Groups In Policy Domainsmentioning
confidence: 64%
“…Through the following steps, actors' preferences about the different policy options were aggregated (Nohrstedt and Ingold 2011; Nownes 2000). First, we calculated the Manhattan distance measure by creating a matrix with actors in the first column and the respective preference for each policy option (on a four‐point Likert scale) in the first row 4 .…”
Section: Resultsmentioning
confidence: 99%